Three-input integralmodel of the recovery problem of antenna signalswith interference - Verlan, Dmytro; Kostian, Nataliia (Publishing House of Lviv Polytechnic National University, 2014)
The problem of increasing the resolution power of an antenna through input signal recovery using the computer implementation of a mathematical model in the form of the system of three Fredholm integral equations of the first kind is examined. To solve the system of linear integral equations, regularizating algorithms and corresponding softwares based on generalized Tikhonov and Lavrentiev methods with determination of a regularization parameter by means of the model experiments technique have been developed. The algorithms are implemented in Matlab environment and can be used with other application packages. The efficiency of the developed computer tools has been confirmed by solving test and practical problems. Розглянуто задачу підвищення роздільної здатності антени шляхом відновлення вхідного сигналу за допомогою комп’ютерної реалізації математичної моделі у вигляді системи трьох інтегральних рівнянь Фредгольма І роду. Для розв’язання системи лінійних інтегральних рівнянь створено регуляризуючі алгоритми та відповідні програмні засоби на основі узагальнених варіантів методів Тихонова і Лаврентьєва з визначенням параметра регуляризації за методом модельних експериментів. Алгоритми реалізовано в середовищі Matlab та їх можна застосувати разом з іншими пакетами прикладних програм. Працездатність розроблених комп’ютерних засобів підтверджується розв’язанням тестових і практичних задач.
Тривходова інтегральна модель задачі відновлення сигналів антени з урахуванням завад
Keywords: signal recovery; antenna; integral equation; regularization; model experiment